Pengaruh Informasi Arus Kas, Laba Bersih dan Pengungkapan Corporate Social Responsibility Pada Volume Perdagangan Saham - Dewi, Ni Putu Sintya Riska; Sari, Maria M. Ratna (E-Jurnal Akuntansi, 2017)
The volume of stock trading is the total number of shares traded within a specified period. Detailed information is the key principal and influence in deciding the action in the activity of buying and selling shares. This research was conducted at the company's textile and garment sector are continuously listed on the Indonesia Stock Exchange 2011-2015. Samples were selected by purposive sampling method. Data analysis technique used is multiple linear regression. F statistical test results show that the model in this study deserve to be used as a regression model. T test results showed that AKOp, Akin, Earnings and CSR affects the volume of stock trading, just AKPn no effect on the volume of stock trading. The test results showed that the coefficient of determination trading volume variance can be explained by the variance information of cash flow, net income and corporate social Responsibility.
Keywords: hares Trading Volume, Information Cash Flow, Earnings and CSR